Critical appraisal of the unmet needs in the treatment of chronic spontaneous urticaria with omalizumab: an Italian perspective. Issue 6 (December 2017) - Asero, Riccardo; Canonica, Giorgio W.; Cristaudo, Antonio; Fierro, Maria T.; Girolomoni, Giampiero; Marzano, Angelo V.; Nettis, Eustachio; Pepe, Patrizia; Pigatto, Paolo; Rossi, Oliviero
Abstract : Purpose of review: The humanized anti-IgE antibody omalizumab has been available for patients with chronic spontaneous urticaria (CSU) in Italy since 2015. This review summarizes the unresolved issues and unmet therapeutic needs associated with omalizumab and discusses practical recommendations for its use in the management of CSU. Recent findings: Although modern second-generation H1 -antihistamines are the standard of care for patients with CSU, adjunctive treatments (including omalizumab) may be required for effective control of symptoms in many patients. Evidence from clinical trials and experience from daily clinical practice suggest that the use of omalizumab in patients with CSU who have inadequate response to H1 -antihistamines remains challenging. Summary: Based on current international guidelines, omalizumab labelling information and our experience in clinical practice, we provide treatment recommendations regarding the use of omalizumab in patients with CSU. These include: optimal treatment duration, the use of concomitant antihistamine therapy, the definition and management of disease relapse after treatment, and the management of patients with late or no response to treatment.